QOLP-02. PATIENT-REPORTED OUTCOMES FOLLOWING PERTUZUMAB PLUS HIGH-DOSE TRASTUZUMAB IN PATIENTS WITH HER2-POSITIVE METASTATIC BREAST CANCER (MBC) AND CENTRAL NERVOUS SYSTEM (CNS) PROGRESSION POST-RADIOTHERAPY. (9th November 2020) - Kumthekar, Priya; Sahebjam, Solmaz; Pegram, Mark; Ibrahim, Nuhad; Sussell, Jesse; Nicholas, Alan; Fung, Anita; Cheng, Anna; Lin, Nancy U
Abstract: Effective therapies are needed for the treatment of patients with HER2-positive MBC who develop brain metastases. In the open-label, phase II PATRICIA study (NCT02536339), 40 patients with HER2-positive MBC with CNS metastases and CNS progression post-radiotherapy (median age 48 years [range, 34–69]; prior CNS treatment [whole brain radiotherapy 71%, stereotactic radiosurgery 59%, both 31%]) were enrolled to receive pertuzumab plus high-dose trastuzumab (6-mg/kg weekly) until CNS or systemic disease progression or unacceptable toxicity. Following a median (range) treatment duration of 4.5 (0.3–37.3) months, the CNS-confirmed objective response rate per Response Assessment in Neuro-Oncology Brain Metastases criteria (primary endpoint) was 11% (95% confidence interval: 3.03, 25.42), and the clinical benefit rate at 4 months was 68%, indicating sustained clinical stability. Patient-reported outcomes (PROs) were evaluated using the MD Anderson Symptom Inventory-Brain Tumor (MDASI-BT), which includes sub-scales for symptom severity (average of 13 core symptom and 9 brain-tumor specific items) and symptom interference (average of 6 interference-with-life items representing overall symptom distress). Among 36 patients included in the PRO analyses, mean (standard deviation [SD]) symptom severity scores at baseline and weeks 12 and 28 were 1.65 (1.62), 2.24 (2.14), and 1.94 (2.55), respectively. Mean (SD) symptom interference scores at baseline and weeks 12 and 28 were 2.51 (2.63), 2.81 (3.39), and 1.76 (2.43), respectively. Mean (SD) changes in symptom severity and interferences scores from baseline to week 12 were 0.34 (1.54) and 0.33 (3.08), respectively. On average, patients who did not achieve stable disease or better in the CNS following treatment had worsened symptom severity and symptom interference scores over 12 weeks, while those with stable disease or better in the CNS exhibited stable or improving scores. Pertuzumab plus high-dose trastuzumab provided clinical benefit to the majority (68%) of patients in PATRICIA, without a decrement in quality of life.